New Age of Indonesian Local Tourism Development: Community Bonding, Youth Work, and Selling Tourism - Hatma Indra Jaya, Pajar; Izudin, Ahmad; Aditya, Rahadiyand (Komunitas, 2022)
This article explores why and how youth can build community bonds in the new era of rural development in Indonesia that produces local works in the form of tourist sales products. This article uses qualitative methods through a case study approach. The research was conducted in Balkondes Wringin Putih. Starting from individual unrest into community bonds that produce youth solidity, the village succeeded in developing tourist destinations in special economic areas based on tourism. When tourism development programs become the country’s priority, youth through the provision of village tour packages can create new jobs and increase rural economic productivity. The community ties and administration in the village’s growth, resulting from the ruralization process, are contextualised in the macro-political structure of the new age of Indonesian rural development, in fact, able to develop youth-based economic resilience. As empirical research to understand the development of new rural tourism, this study learns from the practices in Balkondes about a relational view of the ever-changing mechanisms of community bonding in the modern world.